2011
DOI: 10.1097/ogx.0b013e3182168278
|View full text |Cite
|
Sign up to set email alerts
|

Xenografting of Human Fetal Testis Tissue: A New Approach to Study Fetal Testis Development and Germ Cell Differentiation

Abstract: background: Abnormal fetal testis development can result in disorders of sex development (DSDs) and predispose to later testicular dysgenesis syndrome (TDS) disorders such as testicular germ cell tumours. Studies of human fetal testis development are hampered by the lack of appropriate model, and intervention systems. We hypothesized that human fetal testis xenografts can recapitulate normal development.methods: Human fetal testes (at 9 weeks, n ¼ 4 and 14 -18 weeks gestation, n ¼ 6) were xenografted into male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 31 publications
2
30
0
Order By: Relevance
“…Based on results of the current and previous studies (Orth, 1993;Hochereau-de-Reviers and Perreau, 1997;Yu et al, 2006;Mitchell et al, 2010), it is clear that fetal testis tissue can respond to adult levels of gonadotropins and initiate development. In the current study, xenografts from younger donors showed a tendency for higher growth.…”
Section: Percentage Of Cross Sections Bmentioning
confidence: 76%
See 1 more Smart Citation
“…Based on results of the current and previous studies (Orth, 1993;Hochereau-de-Reviers and Perreau, 1997;Yu et al, 2006;Mitchell et al, 2010), it is clear that fetal testis tissue can respond to adult levels of gonadotropins and initiate development. In the current study, xenografts from younger donors showed a tendency for higher growth.…”
Section: Percentage Of Cross Sections Bmentioning
confidence: 76%
“…When xenografts were collected at 116 and 135 days after surgery, tubule formation was evident and spermatogonial differentiation was observed (Yu et al, 2006). Recently, xenografting of human fetal testis tissue collected between 9 and 18 weeks of gestation to nude mice for 6 weeks was reported to result in tissue survival and differentiation of gonocytes to prospermatogonia (Mitchell et al, 2010). Similar to the ovine study, considering duration of pregnancy and testis development in humans, neither study provided enough time for grafted tissue to undergo full development.…”
mentioning
confidence: 99%
“…Quantification of L1-ORF1p levels demonstrated a significant, concomitant decrease over four weeks following transplant, with levels decreased by ~50% in individual AGCs (Figure 5D) and ~2/3 of VASA + cells devoid of L1-ORF1p (Figure 5E). As most AGCs at this timepoint have entered mitotic arrest (Mitchell et al 2010;Li et al 2017) (data not shown), a decrease in the frequency of L1-ORF1p + cells must arise through degradation of protein, in addition to locusspecific silencing or transcript degradation. To ask whether the decrease in L1-ORF1p levels correlates with an increase in DNA methylation over time, we performed immunostaining for 5methylcytosine (5mC).…”
Section: Declining L1 Expression and Increasing H3k9me3 During Fetal mentioning
confidence: 91%
“…Although we observed increasing nuclear localization of HIWI2 by GW21 (Figure 1C), examination of subsequent events is limited by availability of samples after GW22. We therefore turned to a xenograft model (Mitchell et al 2010;Tharmalingam et al 2018), in which human fetal testis implanted under the kidney capsule of immunocompromised mice will vascularize and continue to grow. Fragments of a single GW17 testis were grafted into separate mice and allowed to grow for 4 and 8 weeks ( Figure 5A).…”
Section: Declining L1 Expression and Increasing H3k9me3 During Fetal mentioning
confidence: 99%
“…Using testes collected at routine castration of, for example, calves to study bovine testis function using TTX into mice, rather than whole animal use of calves, is also consistent with the 3-R principle (i.e., replace, reduce and refine) promoted by many institutional committees on ethical use of animals in research. The use of TTX as a means for testing the developmental potential of a given donor testis after manipulation or as a new diagnostic tool in andrology and related research is already underway (Geens et al 2006, Schlatt et al 2006, Gertow et al 2007, Goossens & Tournaye 2007, Hou et al 2007, Jahnukainen et al 2007a, 2007b, Keros et al 2007, Wyns et al 2007, 2008, Fujita et al 2008, Mitchell et al 2010, Sato et al 2010.…”
Section: Rationale and Potential Applicationsmentioning
confidence: 99%